Clinical Presentation and Causes of Non-traumatic Spinal Cord Injury: An Observational Study in Emergency Patients - Müller-Jensen, Leonie; Ploner, Christoph Johannes; Kroneberg, Daniel; Schmidt, Wolf Ulrich (Frontiers in Neurology, 2021)
Introduction: Diagnosing non-traumatic spinal cord injury (NTSCI) is often challenging. However, clear discrimination from non-spinal pathologies, e.g. “myelopathy-mimics” (MMs), is critical in preventing long-term disability and death. In this retrospective study we (1) investigated causes of NTSCI, (2) identified clinical markers associated with NTSCI and (3) discuss implications for NTSCI management. Methods: Our sample consisted of 5.913 consecutive neurological and neurosurgical patients who were treated in our emergency department during a one-year period. Patients with a new or worsened bilateral sensorimotor deficit were defined as possible NTSCI. We then compared clinical and imaging findings and allocated patients into NTSCIs and MMs. Results: Of ninety-three included cases, thirty-six (38.7%) were diagnosed with NTSCI. Fifty-two patients (55.9%) were classified as MMs. In five patients (5.4%) the underlying pathology remained unclear. Predominant causes of NTSCI were spinal metastases (33.3%), inflammatory disorders (22.2%) and degenerative pathologies (19.4%). 58.6% of NTSCI patients required emergency treatment. Presence of a sensory level (p = < 0.001) and sphincter dysfunction (p = 0.02) were the only significant discriminators between NTSCI and MMs. Conclusion: In our study, one-third of patients presenting with a new bilateral sensorimotor deficit had NTSCI. Of these, the majority required emergency treatment. Since there is a significant clinical overlap with non-spinal disorders, a standardized diagnostic work-up including routine spinal MRI is recommended for NTSCI management, rather than an approach that is mainly based on clinical findings.